Inappropriate oral formulations and information in paediatric trials. Issue 9 (6th July 2010) - Pandit, Sreenivas; Shah, Utpal; Kirby, Daniel Jon; Nunn, Tony; Tuleu, Catherine
Abstract : Previously, quality of formulations information provided for oral medications used in paediatric clinical trials published in 10 highly cited journals between 2002 and 2004 raised concerns. This short report explores if there was any subsequent improvement on how the formulations used in trials involving children <12 years reported in the same journals. Studies published between 2004 and 2008 were hand-searched and classified as containing adequate, some or no formulation information. Those involving solid dosage forms were further analysed. Only 31% (44/140) of publications provided adequate information, 5% less compared to 2002–2004 (28/76). There was a significant 12% rise (p<0.05) of no formulation information at all (37/140) and in tablets/capsules use (53/140), of which 3/4 gave no administration details, even for those under 6 years old, but a 12% decline in suitable paediatric formulations use (52/140 compared to 37/76). Contrary to expectations, overall quality of formulation information reported markedly deteriorated, jeopardising validity of clinical outcomes. The situation may reflect continued lack of awareness among investigators and other stakeholders of the importance of using suitable age-appropriate formulations.